Small CAB-like proteins prevent formation of singlet oxygen in the damaged photosystem II complex of the cyanobacterium Synechocystis sp. PCC 6803 - Sinha, Rakesh Kumar; Komenda, Josef; Knoppová, Jana; Sedlářová, Michaela; Pospíšil, Pavel (Plant, cell & environment, 2012)
The cyanobacterial small CAB-like proteins (SCPs) are single-helix membrane proteins mostly associated with the photosystem II (PSII) complex that accumulate under stress conditions. Their function is still ambiguous although they are assumed to regulate chlorophyll (Chl) biosynthesis and/or to protect PSII against oxidative damage. In this study, the effect of SCPs on the PSII-specific light-induced damage and generation of singlet oxygen ((1)O(2)) was assessed in the strains of the cyanobacterium Synechocystis sp. PCC 6803 lacking PSI (PSI-less strain) or lacking PSI together with all SCPs (PSI-less/scpABCDE(-) strain). The light-induced oxidative modifications of the PSII D1 protein reflected by a mobility shift of the D1 protein and by generation of a D1-cytochrome b-559 adduct were more pronounced in the PSI-less/scpABCDE(-) strain. This increased protein oxidation correlated with a faster formation of (1)O(2) as detected by the green fluorescence of Singlet Oxygen Sensor Green assessed by a laser confocal scanning microscopy and by electron paramagnetic resonance spin-trapping technique using 2, 2, 6, 6-tetramethyl-4-piperidone (TEMPD) as a spin trap. In contrast, the formation of hydroxyl radicals was similar in both strains. Our results show that SCPs prevent (1)O(2) formation during PSII damage, most probably by the binding of free Chl released from the damaged PSII complexes.
Keywords: Chlorophyll; Oxidative Stress; Photosystem II Protein Complex; reaktivní formy kyslíku; oxidační stres; Cytochrome b Group; světlo; tylakoidy; fotosystém I (proteinový komplex); oxidace-redukce; Thylakoids; nízká teplota; singletový kyslík; chlorofyl; bakteriální proteiny; Cold Temperature; Reactive Oxygen Species; Light; fotosystém II (proteinový komplex); hydroxylový radikál; Hydroxyl Radical; cytochromy typu b; Photosystem I Protein Complex; Bacterial Proteins; Oxidation-Reduction; Synechocystis; Singlet Oxygen